Negative symptoms - a real unmet need - I. Soares Da Costa; R. Moreira (European Psychiatry, 2022)
Introduction Schizophrenia is frequently a chronic and disabling disorder, characterized by heterogeneous positive and negative symptoms. Negative symptoms are a major health concern and a core component of schizophrenia that account for a large part of the long-term disability and poor functional outcomes in patients with the disorder. Adequate treatment would mean important progress and Distinguishing primary from secondary negative symptoms may inform about treatment options.